Students' need recognition for higher education at private colleges in Malaysia : an exploratory perspective - Hassan, Faridah Haji; Sheriff, Nooraini Mohamad (Sunway University College, 2006)
The objective of this study is to ascertain the influence of internal and external environmental and marketing stimuli on students? need recognition to study at private colleges in Malaysia. Eight hundred and eighty eight students who were enrolled in 72 multi-disciplined private colleges participated in this study. A two-part questionnaire comprising selected background data, and internal and external stimuli promoting students? need recognition was used. Internal stimuli comprised an individual?s past experience, characteristics and motive. External environmental stimuli encompassed family, reference group and social class; while external marketing stimuli include the quality of programs, promotion, pricing, distribution, lecturers, processes and physical resources. The results indicate that external marketing stimuli have the highest influence on students? need recognition (lecturer?s quality ? 76%; program quality ? 74% and quality of physical resources ? 73%), followed by external environmental stimuli (family ? 70%), and internal stimuli ? 65%. These findings will enable private colleges to formulate effective marketing strategies emphasising students? need recognition and family influence, which will allow them to maintain a sustainable competitive edge over their competitors in this dynamic and highly competitive industry.